2017
DOI: 10.3892/mmr.2017.8242
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of gigantol against hydrogen peroxide‑induced apoptosis in rat bone marrow mesenchymal stem cells through the PI3K/Akt pathway

Abstract: Bone marrow mesenchymal stem cell (BMSC) transplants are promising for the treatment of certain central nervous system diseases. However, oxidative stress is one of the major factors that may limit the survival of the transplanted BMSCs. The present study investigated the effect of pretreatment with gigantol on hydrogen peroxide (H2O2)‑induced apoptosis in rat BMSCs (rBMSCs) and the potential underlying mechanisms. The results demonstrated that gigantol pretreatment significantly inhibited H2O2‑induced apoptos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 31 publications
(26 reference statements)
1
7
0
Order By: Relevance
“…Although the viability of hBMSC was decreased after exposure to the lower concentrations of 125 and 250 µM, these two concentrations had a minimal effect on cellular apoptosis and osteogenic differentiation capacity of hBMSC. In line with our findings, previous study found that the effect of exposure to H 2 O 2 on rat BMSC was also dose-dependent [16]. However, variation among studies in exposure time can contribute to variations in the results, as adverse cellular effects can be induced by lower concentrations of H 2 O 2 when the exposure time is increased [17].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Although the viability of hBMSC was decreased after exposure to the lower concentrations of 125 and 250 µM, these two concentrations had a minimal effect on cellular apoptosis and osteogenic differentiation capacity of hBMSC. In line with our findings, previous study found that the effect of exposure to H 2 O 2 on rat BMSC was also dose-dependent [16]. However, variation among studies in exposure time can contribute to variations in the results, as adverse cellular effects can be induced by lower concentrations of H 2 O 2 when the exposure time is increased [17].…”
Section: Discussionsupporting
confidence: 91%
“…To mimic the microenvironment of oxidative stress detected in various inflammatory bone diseases and to study the effect of oxidative stress on different cell types in vitro, H 2 O 2 exposure is frequently used as a cellular model of oxidative stress [16][17][18]. Although, at low levels, H 2 O 2 has a beneficial role in basic cellular activity such as proliferation and migration, high levels of H 2 O 2 can cause oxidative stress and lead to adverse effects on cell activity [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…We found that these 3 characteristics were negatively affected to a different degree when cells were exposed to H 2 O 2 . In our study, we focused on the loss of stemness, a condition of cellular dysfunction (not apoptosis) induced when stem cells are exposed to a concentration of H 2 O 2 below 600 uM [18]. Stemness plays an important role in the ability of stem cells to self-renew [29], to synthesize extracellular matrix components [30,31], and to differentiate [32].…”
Section: Discussionmentioning
confidence: 99%
“…However, ROS does not always play a damaging role, since recent studies have shown beneficial cell physiological effects at lower concentrations [17]. There have also been many studies investigating methods to protect against oxidative stress and to prevent BMSC apoptosis, such as the use of gigantol [18] or preconditioning with far-infrared irradiation [19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation